2018
DOI: 10.3389/fmicb.2018.02034
|View full text |Cite
|
Sign up to set email alerts
|

Interfering With DNA Decondensation as a Strategy Against Mycobacteria

Abstract: Tuberculosis is once again a major global threat, leading to more than 1 million deaths each year. Treatment options for tuberculosis patients are limited, expensive and characterized by severe side effects, especially in the case of multidrug-resistant forms. Uncovering novel vulnerabilities of the pathogen is crucial to generate new therapeutic strategies. Using high resolution microscopy techniques, we discovered one such vulnerability of Mycobacterium tuberculosis. We demonstrate that the DNA of M. tubercu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 49 publications
(70 reference statements)
0
14
0
Order By: Relevance
“…The chromosome decondensed during novobiocin treatment but shrank rapidly during addition of Ndx. The compaction of the nucleoid is also peculiar, in light of a recent study that showed that decondensation of the mycobacterial chromosome is a common response to a broad spectrum of antimicrobials (74). This confirms that the response to different antibiotics may not be uniform even between the same species and that single-cell studies may give invaluable data concerning various agents.…”
Section: Discussionmentioning
confidence: 99%
“…The chromosome decondensed during novobiocin treatment but shrank rapidly during addition of Ndx. The compaction of the nucleoid is also peculiar, in light of a recent study that showed that decondensation of the mycobacterial chromosome is a common response to a broad spectrum of antimicrobials (74). This confirms that the response to different antibiotics may not be uniform even between the same species and that single-cell studies may give invaluable data concerning various agents.…”
Section: Discussionmentioning
confidence: 99%
“…Sample preparation and imaging was done as previously reported (Scutigliani et al, 2018). Cells were plated on 5 mg mL -1 fibronectincoated glass coverslips and allowed to adhere for 24 hours.…”
Section: Electron Microscopymentioning
confidence: 99%
“…In particular, HupB bends DNA, assists the segregation of newly replicated chromosomes ( Hołówka et al., 2018 ), and localizes toward the new cell pole, as does RNase E. We also find that DNA damage causes a significant fluorescence decrease of both proteins without delocalization, compatible with a stalled fork and chromosomal fragmentation ( Manina et al., 2019 ; Burgess Tornaletti and Manina, 2020 ). In contrast, inhibition of both transcription and translation, causing nucleoid condensation ( Scutigliani et al., 2018 ; Weng et al., 2019 ), delocalizes both HupB and RNase E toward the mid-cell position, with one fluorescence cluster per cell, entailing that RNase E dynamics are largely DNA-dependent, as in C. crescentus ( Montero Llopis et al., 2010 ; Bayas et al., 2018 ). Interestingly, treatment with the cell-wall targeting drug INH causes not only a substantial increase in fluorescence and cell-to-cell fluorescence variation of both RNase E and HupB but also an atypical delocalization toward the cell center, with two main HupB clusters largely superposed by RNase E, suggestive of cell-cycle arrest before septation ( Hołówka et al., 2018 ; Santi and McKinney, 2015 ; Logsdon et al., 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…As rne depletion increases KatG levels, we can speculate that lower RNase E levels are associated with drug activation in individual cells, consistent with increased mortality of M. smegmatis cells experiencing stochastic KatG pulses ( Wakamoto et al., 2013 ). Overall, while too low or too high levels of RNase E and HupB lead to cell death, possibly also due to irreversible DNA compaction ( Scutigliani et al., 2018 ), a dynamic increase followed by the restoration of basal levels of expression is a hallmark of bacilli that better tolerate INH.…”
Section: Discussionmentioning
confidence: 99%